The moderation role of Industry 4.0 towards business performance in manufacturing firms in Malaysia - Nallaluthan, Kesavan; Seyajah, Norhisham; Vengidason, Sethuprakhash; Nashir, Irdayanti Mat; Subramaniam, Tamil Selvan (Ifma Publishing, 2023)
This paper studies the pilot test process on a proposed new model of research and sustainable manufacturing practices for business performance, which is moderated by Industry 4.0. The aim of this pilot study is to assess the usability and reliability of the survey questionnaire. An online survey method was used to collect 116 data from manufacturers in Malaysia. The integration between NRBV and RBV theory is used will provide a more comprehensive model to evaluate manufacturing industries' competitiveness. The results agreed that all the constructs in the proposed model have Cronbach alpha ranges from 0.662 to 0.901, which is evidence of constructs having good reliability and can be used for future research with higher intensity. The result provides useful information for sustainable manufacturing practices which is adopted by manufacturing industries that could affect their usage and further improvement for their business performance during industry 4.0. This study focused on the sustainability in manufacturing practices with Industry 4.0 as a moderator in the Malaysian manufacturing industries. This pilot study is beneficial for the researchers focusing on Industry 4.0 in manufacturing practices.